Complexidade, Espiritualidade e Educação: por uma educabilidade do espírito humano - Araújo, Alan Ricardo de Sousa (2005)
The theme of this research, Complexity, Spirituality and Education: for an educability of the human spirit, suggests that a problematic of understanding of the spirit and human spirituality is rooted not only religious reducts, but also in the actual fiber of science and also in the heart of modern society. We are sure and secure of this not only for its actuality, but because it has gained in these last years indispensable status in the sum total of knowledge, realizations and human ethos. In order, however, to infiltrate this subject, a new epistemological lens capable of a critical, complex, and multidimensional reading with respect to human spirituality is necessary. The genesis of the problem raised by this research stems from the conflict between various perceptions about the human condition that occurs from the crisis experienced today by many scientific tones. The approximation between the theory of complexity, human spirituality with education, allows us to create an enriching scenery that adds quality to our discourses and educational practices in school, in families, in pastoral (community services), in religious education and still in other varied activities. Our nuclear question and that which will serve as the North Star of our efforts in this research is the following: does the human spirit exist, and if it exist, is it educable? For better usage and understanding of this dissertation, the research was divided into three chapters, systematized in the following manner: In the first chapter, we made an exposition of some of the difficulties of infiltration in the thematic about the spirit and human spirituality. This exposition was formed in two moments: the first discusses some conceptual and semantic presuppositions regarding the human spirit and, next, points out the necessity to overcome the fragmented understanding in favor of the recomposition of the human physiognomy (global face). In the second moment, we discoursed about the scientific leveling that pushed aside some human dimensions, under weighty onus for the human existence as a whole. In the second chapter we discussed the actuality of the theme that can also be seen in two parts: in the first we dialogued with some theories about the complexity and multidimensionality of the human condition. Then, we focused beginning with new anthropological dispositions the symbolic and spiritual human dimension. In the second part, we pointed out the disenchantment and crisis of highly progressive society and the emergence and interfaces of topics about human spirituality in these last decades. In the third and last chapter, we discoursed about the functions of the spirit and the real possibilities of an education for the human spirit. In like manner, we divided the chapter in two moments of discussion: in the first, we treated the dimension of the spirit and the expression of the conscience as an function of sense. Following this rationale, we proposed pedagogy turned, also, towards the human spirit. Last, we made a few suggestions that signal an education for human ecology .